IT/Business alignment in practice - Karpovsky, Anna (Henry Stewart Talks, 2019)
IT/business alignment, Business strategy, Alignment practice, Alignment process, Models of alignment, Alignment as translation, Alignment as adaptation, Alignment as experience, Alignment as integration